2005
DOI: 10.1182/blood-2004-07-2938
|View full text |Cite
|
Sign up to set email alerts
|

Phytosphingosine in combination with ionizing radiation enhances apoptotic cell death in radiation-resistant cancer cells through ROS-dependent and -independent AIF release

Abstract: The use of chemical modifiers as radiosensitizers in combination with low-dose irradiation may increase the therapeutic effect on cancer by overcoming a high apoptotic threshold. Here, we showed that phytosphingosine treatment in combination with ␥-radiation enhanced apoptotic cell death of radiation-resistant human T-cell lymphoma in a caspase-independent manner. Combination treatment induced an increase in intracellular reactive oxygen species ( results demonstrate that enhancement of cell death of radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 70 publications
9
86
0
Order By: Relevance
“…Thus, recombinant AIF induces marked pyknosis when added to isolated nuclei or when microinjected into intact cells Loeffler et al, 2001). Moreover, the injection of AIF-neutralizing antibodies or the knockdown of AIF expression with small interfering RNAs has established that endogenous AIF is rate limiting for caspase-independent chromatin condensation induced by apoptotic stimuli (Cregan et al, 2002;Gallego et al, 2004;Kang et al, 2004;Cheung et al, 2005;Park et al, 2005). Condensation of DNA is also documented in vitro, when AIF is added to naked DNA, as shown in this paper.…”
Section: Aif Interactions With Nucleic Acids N Vahsen Et Almentioning
confidence: 52%
See 1 more Smart Citation
“…Thus, recombinant AIF induces marked pyknosis when added to isolated nuclei or when microinjected into intact cells Loeffler et al, 2001). Moreover, the injection of AIF-neutralizing antibodies or the knockdown of AIF expression with small interfering RNAs has established that endogenous AIF is rate limiting for caspase-independent chromatin condensation induced by apoptotic stimuli (Cregan et al, 2002;Gallego et al, 2004;Kang et al, 2004;Cheung et al, 2005;Park et al, 2005). Condensation of DNA is also documented in vitro, when AIF is added to naked DNA, as shown in this paper.…”
Section: Aif Interactions With Nucleic Acids N Vahsen Et Almentioning
confidence: 52%
“…On the one hand, AIF is required for the growth of colon carcinoma cells (Urbano et al, 2005). On the other hand, AIF is required for experimental apoptosis induction, for instance in radiation-resistant human T-cell lymphoma (Park et al, 2005) or in lung or cervix carcinoma (Gallego et al, 2004;Kang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…13,35 Experiments using antioxidants further indicate that ROS acts upstream of Bax relocation and mitochondrial depolarization. 13 We observed that NAC substantially inhibited ROS production, upregulation of p53, conformational changes of Bax, disruption of the DC m , and cell death induction. Nuclear localization of cytochrome c, AIF, and EndoG was detected in all 4-OOH-CY-treated apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear relocation of mitochondrial factors is often preceded by drug-mediated induction of reactive oxygen species (ROS) followed by mitochondrial relocalization of Bax and subsequent mitochondrial disintegration. 13 Cyclophosphamide (CY), a DNA-damaging agent inducing interstrand DNA cross-links, is used in the treatment of lymphomas and autoimmune diseases. 14 CY is a prodrug, which is converted into its active form 4-hydroxy-cyclophosphamide in the liver.…”
mentioning
confidence: 99%
“…10 In mammalian cells, removal of AIF can reduce apoptosis in some particular settings, although there is no general apoptosis defect. 2,8,9 Thus, knockdown of AIF protects differentiated PC12 cells against the neurotoxin 1-methyl-4-phenylpyridinium, 12 Jurkat T lymphoma cells against a combination of g-irradiation and phytosphingosin, 13 16 and Raji B lymphoma cells against UV irradiation. 17 Microinjection of AIF-neutralizing antibodies can also reduce the neurotoxic effects of NMDA in primary murine cortical cultures, 18 the lethal effects of PARP-1 activators in several cellular systems, 19 as well as the proapoptotic effects of staurosporin on non-small cell lung carcinoma cells.…”
mentioning
confidence: 94%